Consumption of anthocyanin-rich Queen Garnet plum juice reduces platelet activation related thrombogenesis in healthy volunteers. (January 2015) - Santhakumar, Abishek Bommannan; Kundur, Avinash Reddy; Fanning, Kent; Netzel, Michael; Stanley, Roger; Singh, Indu
Highlights: Anthocyanin-rich Queen Garnet plum juice (QGPJ) supplementation reduces platelet aggregation and activation dependant platelet surface marker. Intervention with QGPJ prolonged clotting time and reduced fibrinogen concentration. Reduction in oxidative stress marker post QGPJ consumption. Anthocyanins and/or other active metabolites may act as potential anti-platelet therapeutics. Abstract: The anti-thrombotic properties of an anthocyanin-rich Queen Garnet plum juice (QGPJ) and anthocyanin-free prune juice (PJ) were studied in this randomised, double-blind, crossover trial. Twenty-one healthy subjects (M = 10, F = 11) consumed QGPJ, PJ or placebo, 200 mL/day for 28-days followed by a 2-week wash-out period. Only QGPJ supplementation inhibited platelet aggregation induced by ADP (<5%, P = 0.02), collagen (<2.7%, P < 0.001) and arachidonic acid (<4%, P < 0.001); reduced platelet activation-dependent surface-marker P-selectin expression of activated de-granulated platelets (<17.2%, P = 0.04); prolonged activated-partial thromboplastin clotting time (>2.1 s, P = 0.03); reduced plasma-fibrinogen (<7.5%, P = 0.02) and malondialdehyde levels, a plasma biomarker of oxidative stress ( P = 0.016). PJ supplementation increased plasma hippuric acid content ( P = 0.018). QGPJ or PJ supplementation did not affect blood cell counts, lipid profile, or inflammation markers. Our findings suggest that QGPJ but not PJ has the potential to significantly attenuate thrombosis by reducing platelet activation/hyper-coagulability and oxidative stress.